Pendampingan Pengelolaan Keuangan Syariah di BUMDES Sriwijaya Cipta Karya Desa Sadar Sriwijaya - Afifah, Pipit; Wahid, Moh Abdurrahman; Asy’ary, Lathif Hasan (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2026)
In accordance with Government Regulation No. 43 of 2014, Village-Owned Enterprises (BUMDes) play a crucial role in promoting village economic independence through community involvement and capital support from Village Funds. However, BUMDes across the country still face a number of challenges in implementing sharia-compliant financial management, including a lack of human resource knowledge, a lack of technical support, and poor implementation of sharia principles in financial procedures. The Sriwijaya Cipta Karya BUMDes in Sadar Sriwijaya Village, which still uses a traditional financial management system, is also affected by this situation. Through service learning techniques, this Community Service (PKM) project aims to improve the understanding and capabilities of BUMDes managers in implementing sharia-compliant financial management. Using a training approach, lectures, case studies, and practical experience in creating Islamic financial journals and reports, the implementation process included preparation, training/implementation, and evaluation. The results of the activity demonstrated significant improvements in participants' understanding of Islamic accounting and economic principles, the development of Islamic financial Standard Operating Procedures (SOPs), and the capacity of administrators to create financial reports and journals in accordance with Islamic principles. Furthermore, this effort raised public awareness of the importance of sustainable, fair, and halal business practices. Therefore, it is hoped that this mentoring will improve the professional and sustainable financial governance of Village-Owned Enterprises (BUMDes) and serve as a model for Sharia-based village economic management.